"This is my family outside of my family": Care-based relating in a model early college high school - Omer Ari; Teresa Fisher-Ari; Jim Killacky; Roma Angel (Arizona State University, 2017)
Early college (EC) is a novel educational model in the US that combines high school and college in an effort to increase underrepresented students' access to higher education by providing engaging, hands-on instruction in a supportive learning environment. For this phenomenological inquiry, we sought to understand the role of care-based relating in a model early college by examining how relationships are manifested and experienced at this school. Through 30-45 minute interviews, eleven participants (three sophomores, three seniors, and five teachers) described EC teachers' high level of commitment to students' academic success through: (a) responsive instruction in classroom and group contexts; (b) additional learning support for individual students; and (c) varied experiences from traditional school contexts. EC teachers found these efforts fostered student commitment to learning. Additionally, teachers and students noted the extraordinary commitment of EC teachers to the physical, social, and emotional wellbeing of learners demonstrated through: (a) family-like relationships; (b) promoting social and emotional wellbeing through timely advice and intervention; (c) joining students through tragic and intense personal and out-of-school realities; and (d) forming longitudinal connections with students and their families. However, this commitment resulted in teachers taking on significant burden when there was a lack of structural supports available for all learners. Findings hold implications for educational policy and school structuring that can promote educational equity and success through meaningful relationships, responsive practices, wrap-around services for students with out-of-school challenges, and teacher-support structures to ensure the longitudinal development and wellness of teachers, preventing burnout and attrition.